2010
DOI: 10.1097/olq.0b013e3181b76c42
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Surveillance of Rectal Chlamydia and Gonorrhea Among Males—San Francisco, 2005–2008

Abstract: Rectal gonorrhea cases among males remained stable in San Francisco during 2005-2008, but rectal chlamydia increased 38 percent. While testing increased, rectal gonorrhea positivity declined at the STD clinic, and both infections remained stable elsewhere. Sentinel surveillance provides a better understanding of disease trends than case reporting alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…However, this study did not adjust for sexual risk factors or symptomatic presentations. The authors attributed the stable rates of positivity to a significant increase in STI testing rates [34], supporting our hypothesis that increased testing reduces positivity rates in MSM. In contrast to our findings, an Australian MSM cohort study has reported high incidences of urethral and anal chlamydia and gonorrhea.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, this study did not adjust for sexual risk factors or symptomatic presentations. The authors attributed the stable rates of positivity to a significant increase in STI testing rates [34], supporting our hypothesis that increased testing reduces positivity rates in MSM. In contrast to our findings, an Australian MSM cohort study has reported high incidences of urethral and anal chlamydia and gonorrhea.…”
Section: Discussionsupporting
confidence: 85%
“…Marcus et al reported positivity rates at several clinics in San Francisco from 2005 to 2008, and found no change in either anal chlamydia or gonorrhea positivity [34]. However, this study did not adjust for sexual risk factors or symptomatic presentations.…”
Section: Discussionmentioning
confidence: 85%
“…Extragenital infections may also be increasing in prevalence [ 59 , 77 , 95 ], as several studies have reported higher prevalence of extragenital infections among MSM in recent time periods. However, this could also reflect more thorough screening practices or improved testing methods [ 97 , 98 ]. Extragenital infections among MSM are associated with concurrent partners, existing HIV infection ( n = 2 studies), condomless anal sex ( n = 3), and drug use during sex ( n = 1) [ 62 , 65 , 69 , 89 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…In San Francisco, routine screening for gonorrhea and chlamydia at the urogenital, pharyngeal, and rectal sites is widely available for MSM and has been shown to lead to significantly higher rates of gonorrhea and chlamydia diagnoses, primarily through diagnosis of asymptomatic infections [15,16]. After increased rates of syphilis were reported in 2001 and 2002, there have been multiple public health campaigns for routine STI screening of MSM which may partially explain the increased percentage of cases diagnosed in primary care offices during our study period.…”
Section: Discussionmentioning
confidence: 99%